Report of the First Meeting of the Middle East and Eastern Europe Rabies Expert Bureau, Istanbul, Turkey (June 8-9, 2010). (12th September 2011) - Aylan, Orhan; El-Sayed, Aly Fahmy Mohamed; Farahtaj, Firouzeh; Janani, Ali R.; Lugach, Olga; Tarkhan-Mouravi, Olgha; Usluer, Gaye; Vodopija, Rodovan; Vranjes, Nenad; Tordo, Noël; Dodet, Betty
Abstract : Rabies is a threat in all parts of the world where animal reservoirs persists, including Eastern Europe and the Middle East. Rabies experts from seven Middle East and Eastern European countries (Croatia, Egypt, Georgia, Iran, Serbia, Turkey, and Ukraine) met for two days in Istanbul, Turkey (June 8-9, 2010), to exchange information on the epidemiological situation concerning human and animal rabies in their respective countries and to discuss strategies for rabies elimination and control. They decided to establish a regional network, the Middle East and Eastern Europe Rabies Expert Bureau (MEEREB), a regional network of experts, to increase collaboration in rabies prevention and control at the local, regional, and global levels.